Implementation of Ecological Distribution of Venomous Snakes for Clinical Management of Snakebite in Bangladesh - Al Haidar, Ibrahim Khalil; Ghose, Aniruddha; Noman, Mohammed; Rahman, Md Mizanur; Rudra, Sajib; Auawal, Abdul; Islam, Md Rafiqul; Uddin, Md Asir; Md Erfan Uddin, Rabiul Alam; Sayeed, Abdullah Abu; Amin, Md Robed; Ahsan, Md Farid; et al. (Journal of Medicine, 2023)
Background: Snakebite envenoming is a global health problem, mostly in tropical and subtropical countries. Bangladesh is a subtropical country facing thousands of snakebite envenoming death every year. Knowledge of the distribution of venomous snakes is necessary to identify snakebite-prone areas, develop strategies for prevention and management, and reduce venom-induced mortalities and morbidities. Methods: An integrated effort of direct observations of snakes, qualitative analysis of museum specimen records, clinical records of snakebites, and scholarly literature records were used to understand the pattern of distribution of venomous snakes in Bangladesh. Results: We enlist 65 venomous snake species from Bangladesh and present detailed documentation on their distribution pattern. However, only nine species were considered medically relevant species because of their venom potentiality to kill humans and available clinical records of envenomation. The distribution pattern of those species divides the country into two major portions. A portion consists of northern, northwestern, and western parts of the country, which are habitats of Naja naja, Bungarus caeruleus, and B. lividus. Another portion comprised of the northeastern, southeastern, and southern parts of the country provides habitats for N. kaouthia, B. niger, and Trimeresurus erythrurus. However, Daboia. russelii had a different distribution pattern along the bank of the Padma and Meghna, and some coastal districts. Moreover, B. walli had a scattered distribution over the country. The knowledge of this ecological distribution of venomous snakes across the country bears a significant practical effect on clinical management of snakebite. Treating physicians can have a better understanding of possible offending snake species using this knowledge and the clinical syndromes produced by venoms. Conclusion: Pattern of distribution of medically relevant venomous snakes in Bangladesh approaches to initiate concise and specific bite management strategies for two distinct distributional regions of the country. Moreover, the distribution of D. russelii and B. walli demands specific strategies for bite management. J MEDICINE 2023; 24(2): 139-151